Solar Energy Integration for Liquid Palm Sugar Processing in Rural Home-Industry - Wahyu Herwanto; Erwin; Ni Ketut Caturwati; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
This study explicitly aims to evaluate the technical performance and feasibility of a photovoltaic (PV)–battery system in supplying the energy requirements of a liquid palm sugar production machine for rural home-industry applications. Electricity instability in rural areas often disrupts production activities, and although previous studies have demonstrated the potential of solar energy, real-world evaluations for palm sugar processing remain limited. In this research, two 565 Wp solar modules integrated with a 2.2 kW inverter and a LiFePO₄ battery were experimentally tested under actual operating conditions. Real-time data of PV output, irradiance, load demand, and battery condition were recorded. The results show that the PV system consistently supplied 950–1050 W under clear skies and 600–800 W during cloudy conditions, while the battery maintained a stable state of charge (SoC) of 71–85%, ensuring uninterrupted operation. Daily PV energy generation (4.2–4.6 kWh) exceeded load consumption (3.2–3.6 kWh), confirming a positive energy balance. Overall, the system demonstrated stable and reliable performance, indicating that PV–battery integration is feasible for rural MSME-scale liquid palm sugar production.